(untitled) (Journal of Health Sciences, 2015)
Introduction: Glycated hemoglobin (HbA1c) is formed by non-enzymatic binding of glucose to the free amino group of the N-terminal end of the ß-chain of hemoglobin A. HbA1c is representative of the mean blood glucose level over three months. The aim of the study was to evaluate the Hemoglobin A1c immunoturbidimetric assay performance on two different commercial systems.Methods: We evaluated the precision and trueness for determination of HbA1c in whole blood. Concentrations of total hemoglobin and HbA1c were evaluated on Dimension Xpand (Siemens) and Cobas 501 (Roche) analyzers. HbA1c was measured in a latex agglutination inhibition test. Commercial controls Liquichek Diabetes Control Level 1 and Liquichek Diabetes Control Level 2 (Bio Rad) at two levels were used for quality control. Analytical validation of HbA1c included: within-run imprecision, between-day imprecision, inaccuracy and comparison determination on the human samples on 2 systems: Dimension Xpand and Cobas 501 analyzers. Results: Within-run imprecision on the commercially controls for Level 1 is 4.5% and Level 2 is 3.2% between-day imprecision on commercially controls is 6.1% Level 1 and 5.1% Level 2 for respectively inac- curacy on commercially controls for Level 1 is 1.8% and Level 2 is 4.8%. Method comparison on human samples shows the correlation coefficient of 0.99.Conclusion: The presented results of the analytical evaluation methods for the determination of HbA1c showed an acceptable accuracy and precision.